JAMALUDDIN AL-AFGHANI DAN MUHAMMAD ABDUH (TOKOH PEMIKIR DAN AKTIVIS POLITIK DI DUNIA ISLAM MODERN) - KURDI, SULAIMAN (Syariah: Jurnal Hukum dan Pemikiran, 2015)
The position played by Jamaluddin Al-Afghani and Muhammad Abduh in modem Islamicthought highly influential in Muslim countries. Their respects on reason and natural law and God didnot deny them. With Muslim philosophy knowledge background, allow them to influence the teachingof Islam about modernization. They teach things that are recommended by the Muslim philosophy,religion orthodox convey to the general public, and rational divinity to elite community. Their spiritought to imitated. Courage and sense of their responsibility to the people ought to imitated whenIndonesia experienced a slump in all areas of life. They teach how to sacrifice for religion and state.